The Influence of E-Procurement, E-Payment, and E-Commerce on Supply Chain Performance in the Development of Digitalization Innovation at Coffee Shops/Cafes in Surabaya - Suryono, Muhammad Zacky; Palupi, Ghea Sekar (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
This study examines the influence of digitalization on supply chain performance in coffee shops in Surabaya. The research aims to determine whether digitalization has a positive impact on supply chain performance in coffee shops in Surabaya. The study employs a quantitative method based on data from respondents from coffee shops that utilize digitalization. The analysis method used in this study is Structural Equation Modeling (SEM). The results show that e-procurement technology enables coffee shops to purchase raw materials online, while e-payment facilitates customers to make online payments. The results of e-commerce technology can increase operational efficiency, reduce costs, and enhance service quality. Therefore, e-procurement, e-payment, and e-commerce technology can help coffee shops in Surabaya develop digital innovation and improve supply chain performance.